Trading Activity in Colombian Stock Markets. Determinants and evolution 1997-2007 (2019)
We present evidence of the important improvement of the Colombian stock market in terms of trading activity in the last ten years. Indeed, the merger of the former three stock exchanges (Bogota, Medellín and Cali) into the Bolsa de Valores de Colombia in July 2001 can be associated, in an econometric model, to a significant improvement in number for trades for most of the individual stocks. We also explore the determinants and time series regularities of trading activity. Results show that trading activity is strongly positively related to contemporaneous and lagged returns, and is reduced before an macroeconomic announcement, portraying the Colombian stock market as a conservative yet not sophisticated one. Trading activity tend to be lower on Mondays and Fridays and before and after a holiday, and shows a positive end of the year effect. We discuss several explanations for this relations based on the theory and anecdotic observations.